2021
DOI: 10.1002/hep.31497
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cells Induce Ductular Reaction Mimicking Liver Injury in Mice Through Mast Cell–Derived Transforming Growth Factor Beta 1 Signaling: [RETRACTED]

Abstract: Background and Aims Following liver injury, mast cells (MCs) migrate into the liver and are activated in patients with cholestasis. Inhibition of MC mediators decreases ductular reaction (DR) and liver fibrosis. Transforming growth factor beta 1 (TGF‐β1) contributes to fibrosis and promotes liver disease. Our aim was to demonstrate that reintroduction of MCs induces cholestatic injury through TGF‐β1. Approach and Results Wild‐type, KitW‐sh (MC‐deficient), and multidrug resistance transporter 2/ABC transporter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…Interestingly, most mediators secreted by MCs are also SASP components, and several studies have implicated TGF‐β1 in liver disease progression. ( 9,11,29 ) We found that MCs induce IL‐1β expression that was reduced when FXR was inhibited; however, a study by Xiong et al found that obeticholic acid (OCA; FXR agonist), in combination with lipopolysaccharide, ameliorated liver damage and inflammation by decreasing hepatic IL‐1β. ( 30 )…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most mediators secreted by MCs are also SASP components, and several studies have implicated TGF‐β1 in liver disease progression. ( 9,11,29 ) We found that MCs induce IL‐1β expression that was reduced when FXR was inhibited; however, a study by Xiong et al found that obeticholic acid (OCA; FXR agonist), in combination with lipopolysaccharide, ameliorated liver damage and inflammation by decreasing hepatic IL‐1β. ( 30 )…”
Section: Discussionmentioning
confidence: 99%
“…The presence of iMCs in HCC was protective in our cohort, but an excess of mast cells can also be protumorigenic. In particular, introduction of mast cells increased hepatic vascular endothelial growth factor (VEGF)‐A and VEGF‐C formation in a transforming growth factor β1‐dependent manner, ( 47 , 48 ) which can favor angiogenesis, epithelial–mesenchymal transition, and tumor growth. Because cholangiocarcinomas contain about 5 times more mast cells compared to HCC, ( 49 ) protumorigenic effects can prevail in cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…It is apparent that cholangiocyte-derived TGF-β1 is an important factor mediating biliary (autocrine) and liver (paracrine) damage during PSC. Aside from cholangiocytes, mast cells secrete TGF-β1 and induce biliary senescence and other markers of cholestasis (Kyritsi et al, 2021), which is an important feature considering that mast cell migration to portal areas is a key feature and damaging component of cholestasis (Wilcox et al, 1986;Tsuneyama et al, 1999;Jones et al, 2016). Mast cell farnesoid X receptor (FXR) signaling promotes biliary senescence and associated biliary and liver damage in murine models of PSC (Meadows et al, 2021).…”
Section: Primary Sclerosing Cholangitismentioning
confidence: 99%
“…Cholangiocytes are the target of various liver diseases such as fatty liver diseases (nonalcoholic fatty liver disease [NAFLD], non-alcoholic steatohepatitis [NASH]), alcoholic liver disease (ALD) and chronic cholestatic liver diseases including primary biliary cholangitis (PBC), primary sclerosing cholangitis (PSC), biliary atresia, and cholangiocarcinoma. Biliary secretory functions regulate liver inflammation and fibrosis (by both autocrine and paracrine pathways) through secretion of cytokines and other factors which may contribute to liver damage (Kennedy et al, 2021;Kyritsi et al, 2021). Cellular senescence increases in cholangiocytes of PSC patients, likely contributing to disease progression (Tabibian et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%